Survey of optimizing dynamic virtual local area network algorithm for software-defined wide area network - Talah Oday Alani; Ameer Mosa Al-Sadi (Universitas Ahmad Dahlan, 2023)
Software-defined network (SDN) is one of the most predominant technologies for networking in the existing and next-generation networks. Therefore, this paper is conducted to introduce a survey for researchers who are interested in exploiting the dynamic tunneling technique to optimize software-defined wide area network (SD-WAN). The main purpose of this survey is not only to investigate the related works of dynamic tunneling with SD-WAN but also to classify this related work according to the aim of each research into the practicable categories and present the most dominated employments for tunneling with SD-WAN, specifically virtual local area network (VLAN). The performed classification accompany dynamic tunneling in SDN can be summarized into four categories as following: exploring VLAN in SDN; management of multi VLAN in SDN; recover link failure of SDN; and development of SDN by using VLAN. Finally, the intensive study of the literature in this paper discovers that the dominant path of research falls in the class that covers SDN’s link failure. This class takes full advantage of SD-WANs due to offering more robust networking and restoring most communication failures. In the event of a fault, the controller could respond and recover quickly by switching to a pre-computed backup route.